Diagnostic specificity and nonspecificity in the dimensions of preschool psychopathology - Sterba, Sonya (2007)
BACKGROUND: The appropriateness of the Diagnostic and Statistical Manual of Mental Disorders – Fourth Edition (DSM-IV) nosology for classifying preschool mental health disturbances continues to be debated. To inform this debate, we investigate whether preschool psychopathology shows differentiation along diagnostically specific lines when DSM-IV symptoms are aggregated statistically. METHODS: One thousand seventy-three parents of preschoolers aged 2–5 years attending a large pediatric clinic completed the Child Behavior Checklist 1.5–5. A stratified probability sample of 193 parents of high scorers and 114 parents of low scorers were interviewed with the Preschool Age Psychiatric Assessment (PAPA). Confirmatory factor analysis was performed on symptoms from seven DSM disorders. RESULTS: Comparison of competing models supported the differentiation of emotional syndromes into three factors: social phobia (SOC), separation anxiety (SAD), and depression/generalized anxiety (MDD/GAD), and the differentiation of disruptive syndromes into three factors: oppositional defiant/conduct syndrome (ODD/CD), hyperactivity/impulsivity, and inattention. Latent syndrome correlations were moderately high after accounting for symptom overlap and measurement error. CONCLUSIONS: Psychopathology appears to be differentiated among preschoolers much as it is among older children, and adolescents. We conclude that it is as reasonable to apply the DSM-IV nosology to preschoolers as it is to apply it to older individuals.